Percutaneous transluminal balloon pulmonary valvuloplasty: immediate and medium-term results - Özme, Şencan; Çeliker, Alpay; Özkutlu, Süheyla; Özer, Sema; Baysal, Kemal (The Turkish Journal of Pediatrics, 1990)
Ten patients with pulmonary stenosis, (six males and four females) whose ages ranged between five and ten years (mean age 7 years) underwent cardiac catheterization and balloon valvuloplasty. Right ventricular systolic pressure before valvuloplasty ranged from 90 to 200 mm Hg (mean 133.5±33.3 mm Hg). It fell to 50-90 mm Hg (mean 64.5±13.8 mm Hg) immediately after the procedure. The peak systolic gradient across the pulmonary valve before valvuloplasty ranged from 70 to 180 mm Hg (mean 114.5±35.4 mm Hg) and decreased significantly to 30-70 mm Hg (mean 43.0±13.8 mm Hg) immediately after dilation. Doppler echo studies confirmed these results. At repeat cardiac catheterization in three patients, five to 15 months after valvuloplasty, restenosis was noted in one patient while there was no change in the others. All patients had been followed up by Doppler echocardiography. Patients with isolated valvular pulmonary stenosis can be adequately and safely treated with balloon valvuloplasty which results in excellent immediate and medium-term results.